The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00004424-200208000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Radiocontrast-Induced Renal Tubular Cell Apoptosis

Abstract: The radiocontrast/hypertonicity-induced DNA fragmentation of MDCK cells is attenuated by taurine but not by NAC. Because both agents are antioxidants, the antioxidant property is not sufficient for the observed cytoprotective effect. Hence, the antiapoptotic effect of taurine has to be attributed to other, yet to be defined mechanisms. Our results suggest that pharmacological doses of taurine may be particularly protective against RCIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 37 publications
3
90
1
4
Order By: Relevance
“…Moreover, their study also indicated that the disturbance of mitochondrial enzyme activity and mitochondrial membrane potential remained relatively unchanged up to 60 h after iopamidol treatment. As reported in another ex vivo experiment, a highly hyperosmolal, ionic radiocontrast agent diatrizoate can induce DNA fragmentation (apoptosis) in MDCK cells (29). Although we could not determine whether inhibition of mitochondrial function or delayed apoptosis in tubule cells is related to the functional changes in our DW-MR images, it is well known that the deficiency of mitochondrial enzyme activity can reduce the activity of adenosine triphosphate enzyme (ATPase), which may limit the ability of water transport function between extra-and intra-cellular.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, their study also indicated that the disturbance of mitochondrial enzyme activity and mitochondrial membrane potential remained relatively unchanged up to 60 h after iopamidol treatment. As reported in another ex vivo experiment, a highly hyperosmolal, ionic radiocontrast agent diatrizoate can induce DNA fragmentation (apoptosis) in MDCK cells (29). Although we could not determine whether inhibition of mitochondrial function or delayed apoptosis in tubule cells is related to the functional changes in our DW-MR images, it is well known that the deficiency of mitochondrial enzyme activity can reduce the activity of adenosine triphosphate enzyme (ATPase), which may limit the ability of water transport function between extra-and intra-cellular.…”
Section: Discussionsupporting
confidence: 52%
“…Renal damage may also results from direct contrast-induced cytotoxicity or contrast-induced elevations in tissue osmolality (17). In addition, alterations in the metabolism of prostaglandin, nitric oxide, endothelin and adenosine may also play a role in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were housed at [23][24][25] C in a 12-h light/dark cycle with free access to standard rat chow and tap water. All animal experiments were performed with the permission from the Medical Ethics Committee of Tianjin Medical University and followed the protocol outlined in the Guide for the Care and Use of Laboratory Animals published by the US National Institutes of Health (NIH Publication No.…”
Section: Animalsmentioning
confidence: 99%